Differentiating ‘the user’ in DSR: Developing demand side response in advanced economies - Goulden, Murray; Spence, Alexa; Wardman, Jamie; Leygue, Caroline (Elsevier, 2018)
This paper reports on the current state of Demand Side Response (DSR) in the UK – an early adoptor amongst advanced economies – and the role of the end user in determining its future. Through 21 expert interviews we establish the current state of DSR, and expectations for its development. Whilst non-domestic DSR appears healthy, if fragile, domestic DSR is considered to be currently unviable, it's future success dependant on market innovations. In following how that situation is expected to change, we highlight key assumptions about prospective end users. These assumptions are shaping the efforts of the industry actors tasked with delivering DSR. We identify two visions of the user, one passive whilst technologies automate on their behalf, the other integrated to the point of themselves being an automaton. We detail a series of concerns about the limitations of these user visions, and the ability of industry to reach beyond them towards a more differentiated view. We conclude with a call to broaden the institutional landscape tasked with delivering DSR, in order to foster a greater diversity of end user roles, and ultimately greater demand responsiveness from a broader user base.